Movimentos sociais no ciberespaço: uma investigação sobre o ciberativismo - Arruda, Gisele Regina Paes de (2011)
This paper shows a contextualization of changes which has happened in relation to the Social Movements, specially from the 90s, the decade that marked the growth of communication and information technologies usage, bringing a horizontalization of social movements through cyberativism. Thus, the research intended to feature the internet evolution, illustrated by images and maps picked from The Atlas of Cyberspace by Martin Dodge and Rob Kitchin, simultaneously analyzing how the cyberspace has influenced on configuration of these new social movements when it approached these new technologies. Through a comparison and an analysis of some representative social movements, it will be develop a study on the internet role as a way of cyberativism formation in advertisement implementation of causes and society mobilization